Train Operation Monitoring Reveal Safety Management System - ZHANG Zhong-yang; QU Su-rong; ZHANG Xian-feng (机车电传动)
Basic structure, components and main function of the system were expounded. In the system, dispatching order literalretrieval and analysis model was built by using information process technology, with which, railway dispatching order was automaticallyanalyzed, retrieved , and rapidly generated train operation monitoring reveal files. The files was compared to manual editing monitoring revealfiles for finding and correcting its missing and error, which ensured train operation safety.